Physical Design and Mask Synthesis for Directed Self-Assembly Lithography - Shim, Seongbo; Shin, Youngsoo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book discusses physical design and mask synthesis of directed self-assembly lithography (DSAL). It covers the basic background of DSAL technology, physical design optimizations such as placement and redundant via insertion, and DSAL mask synthesis as well as its verification. Directed self-assembly lithography (DSAL) is a highly promising patterning solution in sub-7nm technology.
Introduction -- DSAL Manufacturability -- Placement Optimization for DSAL -- Placement Optimization for MP-DSAL Compliant Layout -- Redundant Via Insertion for DSAL.
Keywords: Nanotechnology; Microtechnology; Microelectromechanical systems; Electronic circuits; Optical materials; Nanoscience; Semiconductors; Nanotechnology; Microsystems and MEMS; Electronic Circuits and Systems; Optical Materials; Nanophysics; Semiconductors